Literasi Kesehatan Reproduksi Sebagai Upaya Peningkatan Pengetahuan dan Sikap Remaja Dalam Menjaga Vulva Hygiene - Hiola, Dewi Suryaningsi; Siti Hajar Salawali; Rachmawaty D. Hunawa; Sitti Fatimah M. Arsad (Bengkulu Institute, 2025)
Vulva hygiene is the act of maintaining and preserving the cleanliness and health of reproductive organs for physical and psychological well-being (Hallimil, Rahmawati, and Maulida 2021). World Health Organization 2019 the incidence of reproductive disorders due to poor vulva hygiene in women is 35%. Data Badan Kependudukan dan Keluarga Berencana Nasional 2020 found that 3.2 million adolescents have reproductive disorders. Good and correct vulva hygiene behavior is needed to improve women's reproductive health. Low knowledge and independent attitudes of reproductive health can endanger adolescent reproductive health. Efforts to increase knowledge and attitudes are through reproductive health literacy activities. The purpose of reproductive health literacy activities is to increase adolescent knowledge and independent attitudes in maintaining vulva hygiene. The results of the implementation have increased adolescent knowledge and independent attitudes in maintaining vulva hygiene.